Ethnobotanical Study of Wild-Edible Plants in Simada District, South Gondar Zone, Amhara Region, Ethiopia - Kindye Belaye Wassie (Ethnobiology Letters, 2024)
This study was conducted in the Simada district, South Gondar Zone, Ethiopia, to investigate the ethnobotanical properties of wild edible plant species. Ethnobotanical data were collected through individual interviews, focus group discussions, guided field walks, and semi-structured questionnaires at markets. The data were analyzed using Microsoft Excel and SPSS version 29.0.2.0. Data were further verified using preference ranking, direct matrix ranking, and informant consensus with buyers, sellers, cooks, and elderly users. A total of 45 edible wild plants from various families were recorded in this investigation. Among the identified wild edible plants, fruit was the most used part (60%), followed by leaves (13%). Most (82%) of the wild edible plants in the study area were consumed raw. There was a significant difference in the number of wild edible plants reported by different informant groups (p<0.05). Opuntia ficus indica was the most frequently used wild edible plant, reported by 69.6% of respondents. Simada District has abundant wild edible plants that poor residents consume and sell to supplement their needs. Strengthening conservation, value addition, and market linking methods will improve local livelihoods and promote sustainable wild edible plant resources management.